PENGAJARAN MORAL DALAM SURAT AL-BAQARAH AYAT 153 - Hamidah, Hamidah (FITRAH:Jurnal Kajian Ilmu-ilmu Keislaman, 2014)
AbstractMoral teaching in surah Al-Baqarah verse 153 isÂ  religious morals of faith, prayer and patience. Faith is a personal believer in the subject matter. In order for the faith sturdy then it must be tested by a variety of exams. Among these exams is fear, hunger, the drawback of property, death, and the lack of fruit. Each test must be faced with patience that the tests come from God and will be revoked and rewarded by God. After that someone must take pray in order to get peace after going through the test.Keyword: Teaching, Moral, Al-Baqarah 153Â AbstrakAjaran moral dalam surat Al-Baqarah ayat 153 adalah moral agama iman, doa dan kesabaran. Iman adalah percaya pribadi dalam materi pelajaran. Agar iman kokoh maka harus diuji oleh berbagai ujian. Di antara ujian ini adalah ketakutan, kelaparan, kekurangan harta, kematian, dan kurangnya buah. Setiap pengujian harus dihadapi dengan kesabaran bahwa tes datang dari Allah dan akan dicabut dan dihargai oleh Allah. Setelah itu seseorang harus mengambil berdoa untuk mendapatkan ketenangan setelah melalui tes.Kata Kunci: Pengajaran, Moral, Al-baqarah 153